Assessing and enhancing emotional well-being in online learning for international undergraduates in China - Zhang, Yue (Journal of International Students, 2025)
The emotional well-being of international undergraduates plays a critical role in their ability to adapt to the demands of online learning. Despite the relaxation of pandemic-related restrictions in China, many international students continue to choose online learning as their preferred mode of study. This study aimed to measure international undergraduates’ online learning interest, self-confidence, and anxiety and reveal the differences in these three online learning emotions across different conditions. A questionnaire survey was conducted among 2,221 international undergraduates from 32 Chinese universities. The results indicated that international undergraduates exhibited a relatively high level of interest in online learning, followed by learning self-confidence. They also suffer from severe learning anxiety. The findings revealed significant differences in online learning interest across different disciplines. Among students with different scholarship conditions, there were substantial differences in both online learning interest and anxiety.